Hyper-Eccentric Structural Genes in the Mitochondrial Genome of the Algal Parasite Hemistasia phaeocysticola. (25th August 2016) - Yabuki, Akinori; Tanifuji, Goro; Kusaka, Chiho; Takishita, Kiyotaka; Fujikura, Katsunori
Abstract: Diplonemid mitochondria are considered to have very eccentric structural genes. Coding regions of individual diplonemid mitochondrial genes are fragmented into small pieces and found on different circular DNAs. Short RNAs transcribed from each DNA molecule mature through a unique RNA maturation process involving assembly and three types of RNA editing (i.e., U insertion and A-to-I and C-to-U substitutions), although the molecular mechanism(s) of RNA maturation and the evolutionary history of these eccentric structural genes still remain to be understood. Since the gene fragmentation pattern is generally conserved among the diplonemid species studied to date, it was considered that their structural complexity has plateaued and further gene fragmentation could not occur. Here, we show the mitochondrial gene structure of Hemistasia phaeocysticola, which was recently identified as a member of a novel lineage in diplonemids, by comparison of the mitochondrial DNA sequences with cDNA sequences synthesized from mature mRNA. The genes of H. phaeocysticola are fragmented much more finely than those of other diplonemids studied to date. Furthermore, in addition to all known types of RNA editing, it is suggested that a novel processing step (i.e., secondary RNA insertion) is involved in the RNA maturation in the mitochondria of H. phaeocysticola . Our findings demonstrate the tremendous plasticity of mitochondrial gene structures.